Factors Affecting the Quality of Sleep Quality in the Elderly - Herawati, Novi; Syahrum, Syahrum (GLOBAL HEALTH SCIENCE GROUP, 2024)
Aging is a process that occurs throughout life. As age increases, various body functions including the neurological system in the form of the number and size of neurons decrease, resulting in a decrease in the function of norepinephrine which ultimately has an impact on the sleep quality of the elderly. Various factors are related to sleep quality, including the physical condition of the elderly, the emotional stress they experience and environmental factors. The research aims to determine factors related to sleep quality in the elderly. The research is descriptive analytic with a cross sectional approach. The population was 123 people, with a sample of 96 people selected through probability simple random sampling. Interviews were conducted in a structured manner to obtain data. Research shows that 79.2% of respondents had poor sleep quality, 67.7% of respondents experienced physical illness and 55.2% of respondents had an uncomfortable environment and 66.7% of respondents experienced emotional stress. There is a relationship between sleep quality and physical pain, the environment and emotional stress. With the results of the chi square test, elderly sleep quality is influenced by physical illness (with a p value of 0.000), the environment (with a p value of 0.022) and emotional stress (with a p value of 0.041). For the health services, they are activating posyandu for the elderly to monitor the health of the elderly and improve the abilities of the elderly through environmental education and stress management education to improve the sleep quality of the elderly. For further research as basic data for research as basic data for research on sleep quality in the elderly.